(net.art) : Materialien zur Netzkunst. - Baumgärtel, Tilman (Nürnberg : Verlag für moderne Kunst, 1999)
X, Robert Adrian ; Rena Tangens & padeluun ; Idensen, Heiko ; Staehle, Wolfgang ; van der Cruijsen, Walter ; Pierce, Julianne ; Wohlgemuth, Eva ; Stelarc ; Garrin, Paul ; Vesna, Victoria ; Jodi ; Bunting, Heath ; Shulgin, Alexei ; Lialina, Olia ; Peljhan, Marko ; Cosic, Vuk ; Sifuentes, Roberto ; Gomez-Pena, Guillermo ; Fuller, Matthew ; Sollfrank, Cornelia
Bibliografie
Duits
boek